2006
DOI: 10.1038/nsmb1110
|View full text |Cite
|
Sign up to set email alerts
|

Separate RNA-binding surfaces on the multifunctional La protein mediate distinguishable activities in tRNA maturation

Abstract: By sequence-specific binding to 3' UUU-OH, the La protein shields precursor (pre)-RNAs from 3' end digestion and is required to protect defective pre-transfer RNAs from decay. Although La is comprised of a La motif and an RNA-recognition motif (RRM), a recent structure indicates that the RRM beta-sheet surface is not involved in UUU-OH recognition, raising questions as to its function. Progressively defective suppressor tRNAs in Schizosaccharomyces pombe reveal differential sensitivities to La and Rrp6p, a 3' … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
191
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(207 citation statements)
references
References 40 publications
14
191
0
2
Order By: Relevance
“…Since the typical RNA interaction surface of the central RRM, a four-stranded antiparallel β-sheet, does not contact the 3´ uridylates (Teplova et al 2006), it could stabilize other pre-tRNA elements. Consistent with this hypothesis, conserved residues in the RRM are necessary for maturation of several structurally impaired pre-tRNAs in Schizosaccharomyces pombe (Huang et al 2006). Similarly, as the usual surface used by winged helix domain proteins to recognize double-stranded DNA is not involved in binding of La to 3´ ends (Dong et al 2004;Teplova et al 2006), this surface may be involved in other interactions.…”
Section: La Stabilizes Nascent Noncoding Rnas and Assists Pre-trna Fosupporting
confidence: 55%
“…Since the typical RNA interaction surface of the central RRM, a four-stranded antiparallel β-sheet, does not contact the 3´ uridylates (Teplova et al 2006), it could stabilize other pre-tRNA elements. Consistent with this hypothesis, conserved residues in the RRM are necessary for maturation of several structurally impaired pre-tRNAs in Schizosaccharomyces pombe (Huang et al 2006). Similarly, as the usual surface used by winged helix domain proteins to recognize double-stranded DNA is not involved in binding of La to 3´ ends (Dong et al 2004;Teplova et al 2006), this surface may be involved in other interactions.…”
Section: La Stabilizes Nascent Noncoding Rnas and Assists Pre-trna Fosupporting
confidence: 55%
“…Because trz1 is essential, we used a strain carrying a temperature-sensitive allele of trz1 (trz1-1) (39) to evaluate the role of trz1 in nuclear tRNA 3Ј-end processing. We examined the processing of two well characterized nuclear tRNAs (tRNA AAC Val and tRNA CUU Lys ) in the trz1-1 and wild-type strains by Northern blotting using the intron-specific and mature oligonucleotide probes as described previously (5,39,(42)(43)(44)(45). These two tRNAs are encoded by the most abundant intron-containing tRNA genes in S. pombe, and thus, their processing intermediates can be easily detected.…”
Section: Inactivation Of Trz1 Affects 3ј-end Processing Of Nuclear Trmentioning
confidence: 99%
“…tRNA processing and modification steps include removal of 5Ј-and 3Ј-extensions, splicing of introns (for only a subset of nuclear pre-tRNAs), base modifications, and addition of 3Ј-CCA sequence (2)(3)(4). For most nuclear pre-tRNAs, 5Ј-end processing occurs prior to 3Ј-end processing, and binding by the conserved La protein to pre-tRNAs is required for the orderly processing of tRNA and for the endonucleolytic processing of pre-tRNA 3Ј-ends (5,6). In the absence of the yeast La protein, the 3Ј-end of nuclear tRNA is matured by exonuclease Rex1p (7,8).…”
mentioning
confidence: 99%
“…Studies of tRNA maturation in budding and fission yeasts have resulted in a model in which La sequesters pre-tRNA 39 ends from exonucleases, favoring trailer removal by an endonuclease (Van Horn et al 1997;Yoo and Wolin 1997;Huang et al 2006). Although the identity of the endonuclease that matures the trailer in yeast has not been reported, work in other organisms has revealed that pre-tRNA trailers are removed by the endonuclease RNase Z (Redko et al 2007;Spath et al 2007).…”
Section: Introductionmentioning
confidence: 99%